2002
DOI: 10.1152/jn.00765.2001
|View full text |Cite
|
Sign up to set email alerts
|

Taste Responses of Neurons of the Hamster Solitary Nucleus Are Enhanced by Lateral Hypothalamic Stimulation

Abstract: . Taste responses of neurons of the hamster solitary nucleus are enhanced by lateral hypothalamic stimulation. J Neurophysiol 87: 1981-1992, 2002; 10.1152/jn.00765.2001. Gustatory responses in the brain stem are modifiable by several physiological factors, including blood insulin and glucose, intraduodenal lipids, gastric distension, and learning, although the neural substrates for these modulatory effects are not known. Stimulation of the lateral hypothalamus (LH) produces increases in food intake and altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 50 publications
(81 reference statements)
2
45
1
Order By: Relevance
“…Electrical stimulation of the BNST modulated taste responses in the NST and PbN (34,74). Activation of the CeA and LH also modulated taste responses of the neurons in the NST and PbN (8,35,36). Modulation of PbN neurons' taste responses by forebrain activation, including the CeA, LH, and GC, has also been demonstrated by Lundy and Norgren (39,40) in the rat.…”
Section: Discussionmentioning
confidence: 69%
“…Electrical stimulation of the BNST modulated taste responses in the NST and PbN (34,74). Activation of the CeA and LH also modulated taste responses of the neurons in the NST and PbN (8,35,36). Modulation of PbN neurons' taste responses by forebrain activation, including the CeA, LH, and GC, has also been demonstrated by Lundy and Norgren (39,40) in the rat.…”
Section: Discussionmentioning
confidence: 69%
“…Bereiter and coworkers (Bereiter et al, 1980) were the first to demonstrate that NTS neurons receiving oral input through the chorda tympany nerve are modulated by lateral hypothalamic stimulation. Such facilitation of gustatory responses in NTS neurons by lateral hypothalamic stimulation was recently confirmed in the hamster (Cho et al, 2002). Rogers and coworkers then demonstrated a similar effect of paraventricular nucleus stimulation on the activity of NTS neurons receiving gastrointestinal afferents through the vagus nerve (Rogers and Hermann, 1985).…”
Section: Integration Of Vagal Mechanisms In the Forebrainmentioning
confidence: 75%
“…Prior studies demonstrated that stimulation in the LH and CeA can alter responses of nucleus of the solitary tract neurons (NST) to sapid stimulation (Cho et al 2002a;Li et al 2002), whereas the effects of only CeA stimulation were tested one synapse further centrally in the PBN (Lundy and Norgren 2001). Recent evidence also indicates that descending input from the LH and CeA converge to modulate some of the same NST taste cells (Cho et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…All 3 forebrain areas modulate the same system bilaterally (Cho et al 2002a;DiLorenzo and Monroe 1995;Li et al 2002). In fact, contralateral stimulation of the CeA and GC, but not the LH, more effectively suppressed responses in NaCl-best PBN cells than did ipsilateral activation.…”
Section: Bilateral Modulation Of Taste Processingmentioning
confidence: 93%
See 1 more Smart Citation